Assessment of Bone Healing During Antegrade Intramedullary Rod Femur Lengthening Using Radiographic Pixel Density. Issue 18 (15th September 2018) - Vulcano, Ettore; Markowitz, Jonathan S.; Ali, Shabaz; Nguyen, Joseph; Fragomen, Austin T.; Rozbruch, S. Robert
Abstract : Introduction: Premature full weight bearing after femur lengthening can lead to implant failure, telescopic nail shortening, and regenerate fracture. This study aimed at performing a retrospective analysis of the correlation between pixel density ratio (PDR) calculations and clinical readiness for weight bearing in patients undergoing intramedullary nail–mediated femoral distraction osteogenesis. Methods: Thirty-two patients who underwent antegrade femur lengthening were included in this study. The PDR was calculated on femur radiographs in a picture archiving and communication system for each cortex (ie, medial, lateral, anterior, and posterior) at each postoperative visit. These values were then correlated with subjective evaluation of bone healing by the treating physician with expertise in bone lengthening. Results: Bone regenerate healing was clinically declared by the treating surgeons (S.R.R. and A.T.F.) at a mean of 8.5 weeks (range, 4 to 18 weeks). No implant failure, nail shortening, or regenerate fracture was observed. The overall mean PDR corresponding to clinical bone healing was 0.90, which was significantly ( P < 0.001) greater than the mean value at the previous visit (0.82), when the bone was not clinically declared to be healed. The PDR increased in all cortices at all postoperative visits. Conclusions: The findings of the present study suggest that there may be a correlation between the PDR and clinical bone healing. This observational pilot study should be followed by additional studies to understand the relationship between the PDR and bony union.